Optimizing kick rate and amplitude for Paralympic swimmers via net force measures - Fulton, S. K.; Pyne, D.; Burkett, B. (Journal of Sports Sciences, 2011)
Kicking is a key component of freestyle swimming yet the optimum combination of kick rate and kick amplitude remains unknown. For Paralympic swimmers, with upper and lower limb disabilities, the influence of the kick plays an important role in net force production. To determine optimum kick characteristics, 12 Paralympic swimmers aged 19.8 ± 2.9 years (mean ± s) were towed at their individual peak freestyle speed. The experimental conditions were (i) a prone streamline glide for passive trials and (ii) maximal freestyle kicking in a prone streamline for active trials at different speeds and kick amplitudes. Kick rate was quantified using inertial sensor technology. Towing speed was assessed using a novel and validated dynamometer, and net force was assessed using a Kistler force-platform system. When peak speed was increased by 5%, the active force increased 24.2 ± 5.3% (90% confidence limits), while kick rate remained at 150 kicks per minute. Larger amplitude kicking increased the net active force by 25.1 ± 10.6%, although kick rate decreased substantially by 13.6 ± 5.1%. Based on the current kick rate and amplitude profile adopted by Paralympic swimmers, these characteristics are appropriate for optimizing net force.